2008
DOI: 10.1097/gim.0b013e3181634edf
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone reserve in 22q11.2 deletion syndrome

Abstract: Objective: We hypothesized that most patients with 22q11.2 deletion and a history of hypocalcemia have inadequate parathyroid function, manifested by intact parathyroid hormone levels below normal. We aimed to evaluate intact parathyroid hormone levels both during normocalcemia and at hypocalcemia, in this population.Study Design: Retrospective chart review of 103 patients with 22q11.2 deletion born since 1997 and cared for at the Children's Hospital of Philadelphia. Calcium and intact parathyroid hormone draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
3
22
1
1
Order By: Relevance
“…Kapadia et al . concluded that hypocalcemia in 22qDS patients is caused by a decrease in the PTH reserve in response to stressors …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kapadia et al . concluded that hypocalcemia in 22qDS patients is caused by a decrease in the PTH reserve in response to stressors …”
Section: Discussionmentioning
confidence: 99%
“…The presence of neonatal hypocalcemia was not predictive of postnatal hypocalcemia in the present study. It has been reported that neonatal hypocalcemia is associated with the later development of permanent hypoparathyroidism . Another study has reported that 13–30% of 22qDS patients have possible hypoparathyroidism outside of the neonatal period .…”
Section: Discussionmentioning
confidence: 99%
“…Hypocalcemia is reported in approximately 50%–69% of patients with 22q11.2DS and is caused by agenesis or hypoplasia of the parathyroid glands, which are derivatives of the third and fourth pharyngeal pouches (Weinzimer, 2001). Hypoparathyroidism in this condition generally seems to be a result of decreased PTH reserve, with a predisposition to develop hypocalcemia during periods of stress or illness (Kapadia, Kim, McDonald-McGinn, Zackai, & Levitt Katz, 2008). Other endocrine manifestations include hypothyroidism, Graves’ disease, and growth hormone deficiency (Choi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As originally described by DiGeorge, hypocalcaemia was attributed to aplasia or hypoplasia of the parathyroid glands due to a developmental defect. There are however few reported supporting autopsy findings to document structural parathyroid defects in 22q11·2DS . The analysis of the PTH response to ionized calcium in individuals with 22q11·2DS in our study suggests that the parathyroid glands were not completely dysfunctional but displayed variable (often poor) efficiency of response, likely related to reduced PTH reserve, in these subjects.…”
Section: Discussionmentioning
confidence: 45%